Presença e representação dos povos indígenas na arte pública capixaba - Oliveira, Jaqueline Torquatro de (2025)
This dissertation, presented to the Graduate Program in Arts at UFES, aims to analyze the presence and modes of representation of various Indigenous ethnic groups in public art in Espírito Santo. The research investigates the arrival of Europeans in Latin America and the impacts of colonization and the actions of the Catholic Church, highlighting the processes of transculturation resulting from memoricide, genocide, and ethnocide. These factors contributed to the modification of cultural identity and the erasure of pre-Columbian Indigenous traditions. Furthermore, the study discusses how the development of art in Brazil, shaped by European influences, has affected society’s perception of Indigenous peoples. Since colonization, Indigenous individuals have been represented according to the imagination of European settlers and clergy, which has influenced how their identities have been constructed and disseminated in the public sphere. The research analyzed artworks present in public spaces in Espírito Santo, classifying them into categories such as Indianist, pre-Indigenist, Indigenist, and others, with the latter suggested for future investigations. The study covers Indigenous representations from the artistic period dominated by the Jesuits (1557–1759) to the presence of mythologized figures and allegories in neoclassical-style monuments that began to be incorporated into public spaces from 1868 onward. Finally, this dissertation proposes an in-depth analysis of these categories, seeking to break away from the hegemonic perspective that has dominated Brazilian art since colonization and to contribute to a critical reading of Indigenous representation in public art in Espírito Santo.